The first El Salvador sites and services project summary of the main findings of a five-year evaluation - Bamberger, Michael (Philippine Journal of Public Administration, 1981)
As a response to the deficit in urban housing in El Salvador brought about by low housing production and increasing percentage of houses needing improvement/ replacement, the First El Salvador Sites and Services Project was executed by the Fundacion Salvadorena de Desarollo y Vivienda Minima (FSDVM). The FSDVM project seeks to increase the annual production of public housing and to introduce changes to existing policies related to urban shelter and city planning. A five-year evaluation of the project was conducted revealing that FSDVM is achieving most of its objectives and that it is the cheapest option available to low-income families in comparison with all other types of housing program in the country. Recommendations covering project design, financing and implementation to improve program strategies to make housing accessible to the urban poor are discussed.